2014
DOI: 10.18579/jpcrkc/2014/13/2/78403
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Thin Layer Chromatographic Method for the Simultaneous Quantitation of Melatonin and Zolpidem in Tablet formulation

Abstract: A simple, accurate and precise densitometry method for the simultaneous estimation melatonin (MEL) and zolpidem (ZOL) in pharmaceutical dosage forms has been developed and validated. Separation of drugs was carried out using toluene: n-butanol: glacial acetic acid: water (1:4:2:2v/v/v/v) as mobile phase on precoated Silica Gel 60F plates. The densitometry evaluation of spot was carried out at 254 nm. The R 254 f value for MEL and ZOL were found to be 0.87±0.01 and 0.59±0.01 respectively. The method was validat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 5 publications
0
0
0
Order By: Relevance
“…Anand et al, 2009) [62] . In Maharashtra among the population density of fruit piercing moth in harvesting season of citrus fruits moths belong to Eudocima: Erebidae found the most (Mohite and Deshmukh, 2014) [63] . At Bangalore, the identification of gut bacteria has been done to compare gut microbial flora of Tomato fruit borer Helicoverpa armigera of the wild and laboratory habitat from fourth and fifth instars by 16s rRNA gene sequencing, concluded that habitat impacts on gut microbial flora, founded variation in the bacterial species (S. Madhusudan, S. K. Jalali, et al 2011) [36] .…”
Section: Microbiota Of Various Moth Pestsmentioning
confidence: 99%
“…Anand et al, 2009) [62] . In Maharashtra among the population density of fruit piercing moth in harvesting season of citrus fruits moths belong to Eudocima: Erebidae found the most (Mohite and Deshmukh, 2014) [63] . At Bangalore, the identification of gut bacteria has been done to compare gut microbial flora of Tomato fruit borer Helicoverpa armigera of the wild and laboratory habitat from fourth and fifth instars by 16s rRNA gene sequencing, concluded that habitat impacts on gut microbial flora, founded variation in the bacterial species (S. Madhusudan, S. K. Jalali, et al 2011) [36] .…”
Section: Microbiota Of Various Moth Pestsmentioning
confidence: 99%